Registration of 'Faraj', a Hessian fly– and multiple disease–resistant durum wheat cultivar in Morocco. Issue 2 (14th April 2022) - Nsarellah, N.; Nachit, M.; Taghouti, M.; Lhaloui, S.; Amamou, A.
Abstract: Durum wheat [ Triticum turgidum L. ssp. durum (Desf.)] is cultivated on nearly one million hectares in Morocco.About half of the durum‐planted areas are located in unfavorable rainfed areas. The predominant abiotic stresses are drought and heat, and the predominant biotic stresses are Hessian fly, leaf rust, tan spot, Septoria blotch, and root rot. End use grain quality‐related traits are important. 'Faraj' (Reg. no. CV‐1190, PI 699898) is a durum cultivar that possesses adaptation to drought and genetic resistance to Hessian fly, leaf rust, tan spot, and Septoria leaf blotch and tolerance to root rot. Faraj possesses good levels of grain yellow pigment and grain protein concentration. Faraj was registered in 2007 and released to seed commercialization in 2014. Faraj could be used by breeders as a good genetic resource with grain yield potential and end use quality as well as resistance or tolerance to multiple diseases and pests.